Infrared spectroscopy of solid normal hydrogen doped with CH₃F and O₂ at 4.2 K: CH₃F:O₂ complex and CH₃F migration - Abouaf-Marguin, L.; Vasserot, A.-M. (Физика низких температур, 2011)
Double doping of solid normal hydrogen with CH₃F and O₂ at about 4.2 K gives evidence of (ortho-H₂)n:CH₃F clusters and of O₂:CH₃F complex formation. A FTIR analysis of the time evolution of the spectra, in the ν₃ C–F stretching mode region, points out a behavior of the clusters very different from that of (ortho-H₂)n:H₂O clusters. The main point is the observation of CH₃F molecules migration in solid para-H₂ at 4.2 K, which is a behavior different from H₂O in identical experimental conditions. This is proved by the increase with time of the CH₃F:O₂ complex integrated intensity with a rate constant K=2.7(2) ⋅10⁻⁴s⁻¹.